Tourism and Biodiversity in Natura 2000 Sites. Case Study: Natura 2000 Valea Roșie (Red Valley) Site, Bihor County, Romania - Dorina Camelia Ilieș; Grigore Herman; Alexandru Ilies; Ștefan Baias; Olivier Dehoorne; Sorin Buhaș; Răzvan Dumbravă; Raluca Buhaș; Ioana Josan; Horia Carțiș; Mihaela Ungureanu (Études Caribéennes)
The paper focuses on investigation of the importance of nature and development of tourism in protected areas. Therefore, in this context a new challenge is emerging: the need to conserve and protect bio and geo diversity, as well as the economic valorisation of these areas based mainly on tourism and leisure. At EU level, Natura 2000 protected areas have developed, implemented and cultivated the need to practice sport and recreational activities in these areas both for spending leisure time and also as stress antidote. The recreational and sporting practices that can be undertaken within the ecological network Natura 2000 sites adapted to the specificity of each protected area, in close connection with the environmental conditions. For the preservation of the natural environment should develop and maintain a close collaboration with tourism and sports associations that organize such activities in those areas.